2012
DOI: 10.1021/la300819u
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Protein Adsorption on a Nanoparticulated Gold Film by Attenuated Total Reflection Surface-Enhanced Infrared Absorption Spectroscopy

Abstract: In situ surface enhanced infrared absorption spectroscopy (SEIRAS) with an attenuated total reflection (ATR) configuration has been used to monitor the adsorption kinetics of bovine hemoglobin (BHb) on a Au nanoparticle (NP) film. The IR absorbance for BHb molecules on a gold nanoparticle film deposited on a Si hemispherical optical window is about 58 times higher than that on a bare Si optical window and the detection sensitivity has been improved by 3 orders of magnitude. From the IR signal as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 54 publications
3
42
0
Order By: Relevance
“…Protein adsorption on AuNP has been reported to deviate from simple Langmuir adsorption previously. 3,25 It is likely that hemoglobin forms at least partial multilayers already at the comparatively low protein concentrations used here. 26 Multilayer formation explains why the BET isotherm provides the best fit of our protein adsorption data ( Figure 4).…”
Section: Hemoglobin Layer Structurementioning
confidence: 96%
“…Protein adsorption on AuNP has been reported to deviate from simple Langmuir adsorption previously. 3,25 It is likely that hemoglobin forms at least partial multilayers already at the comparatively low protein concentrations used here. 26 Multilayer formation explains why the BET isotherm provides the best fit of our protein adsorption data ( Figure 4).…”
Section: Hemoglobin Layer Structurementioning
confidence: 96%
“…Adsorption of hemoglobin (Hb) on naked gold nanoparticles or SAM-modified gold electrodes was studied by monitoring the time resolved evolution of amide signals [69,70]. Results showed that both the electrostatic interaction and the coordination bonds between bovine hemoglobin (BHb) residues and Au NP film surface affected the adsorption kinetics.…”
Section: Adsorption and Conformation Changesmentioning
confidence: 99%
“…The maximum adsorption was obtained at solution pH 7.0. Due to these irreversible interactions and non-uniformed surface structure of gold nanoparticles, the adsorption process of BHb on gold nanoparticle film can be better described by the Freundlich adsorption equation [69]. The immobilization of Hb on PO 3 H 2 -terminated SAMs followed a relatively sluggish process due to the formation of multilayer Hb structures [70].…”
Section: Adsorption and Conformation Changesmentioning
confidence: 99%
“…Surface-enhanced infrared adsorption spectroscopy (SEIRAS) is an effective detection method to study the secondary structure of proteins in a super-thin layer adsorbed onto a nano-Au film [13][14][15]. The vibration of the adsorbed molecules or proteins can be enhanced by more than 2 orders of magnitude, which solves the problem in poor sensitivity of conventional IR spectroscopy.…”
mentioning
confidence: 99%
“…Moreover, SEIRAS not only can in-situ and real-time monitor adsorption of proteins onto biomimic membranes [13,15,16], but also can detect the change in the adsorption properties of proteins and biomimic membranes induced by interaction with nanoparticles [17]. By combining with electrochemistry, potential-induced SEIRA difference spectroscopy can finely reflect some very small changes of the secondary structure and component groups of redox proteins during the process of electron acceptance and donation [12,18].…”
mentioning
confidence: 99%